TITLE: DIGITAL STORYTELLING: A CONTEMPORARY METHODOLOGY FOR IMPROVING LANGUAGE ABILITY IN YOUNGSTERS (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2025)
This full-length article focuses on the concept of digital storytelling as a modern teaching tool that greatly enhances English language learning abilities among young language learners. By referring to recent studies on multimedia learning theory and cognitive psychology in a technology-integrated learning environment, this article explores how digital storytelling develops speech, listening, reading, and writing abilities among children. This article focuses on how engaging and cognitive learning environments for children are developed using multimodal content, storytelling techniques, and accessible technology for children while providing a teaching guide for teachers to effectively use digital storytelling in class to develop language skills and 21st-century learning abilities among children. Emotional involvement, autonomy, teamwork learning, and awareness about technology are identified as critical elements of modern ESL learning environments using digital storytelling.